Analisis Struktur Pasar dan Strategi Penetapan Harga Produk Baru dalam Persaingan Monopilistik - Irawan, Fajar Rayhan Putra; Arifianto, Teguh; Zefriyenni, Zefriyenni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze market structure and pricing strategies for new products in the context of monopolistic competition through a literature review approach. The method applied is a systematic literature review of scholarly articles, textbooks, and empirical research published between 2020 and 2025. The findings reveal that in monopolistic markets, firms possess limited pricing power due to product differentiation and demand elasticity. Classical strategies such as skimming and penetration pricing remain relevant but have evolved in the digital era into data-driven practices such as dynamic pricing and machine learning–based optimization. While these strategies enhance revenue potential, they also introduce risks such as algorithmic collusion and fairness issues that demand regulatory oversight. The implications highlight the necessity for firms to adopt adaptive, data-driven, and ethically responsible pricing strategies, while policymakers should ensure proper regulation to maintain healthy market competition.